Analysis of human cytomegalovirus nucleoprotein complexes. - St Jeor, S (1982)
When chromatin was isolated from cells infected with human cytomegalovirus, the virus DNA remained with the chromatin fraction. If deproteinized virus DNA was added to either isolated nuclei or chromatin, the DNA was lost during the chromatin isolation. When isolated chromatin from cytomegalovirus-infected cells was banded in isopycnic metrizamide gradients, a single peak with a density of 1.18 g/cm3 was present. Analysis of this peak in isopycnic neutral CsCl gradients indicated that it contained both human cytomegalovirus and human embryonic lung cell DNAs. When infected nuclei were treated with micrococcal nuclease, 11S subunit particles which cosedimented with cell nucleosomes and contained virus DNA were isolated.